Pemberdayaan Masyarakat Dalam Menumbuhkan dan Meningkatkan Kompetensi Berwirausaha Pasca Pandemi COVID-19 - Agus Khazin Fauzi; Baiq Desthania Prathama; Sopian Saori; I Nengah Arsana; Yusi Faizhatul Octavia (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Since the occurrence of Covid-19, many people in the surrounding community have lost their jobs or the bussines they are involved in have closed so that the impact on income has decsreased. As an effort to overcome this,in order to survive and produce an economy for the family, it is necessary that the community has entrepreneurial competencies including innovation and creativity. Because, so far in the field there are still many hamlet or village potentials that have not been optimized. On the other hand, there are many business actors who have been around for a long time but the haven't developed because they are not well known by the wider community. Through this community service, the community is empowered by being trained to utilize waste glass bottles or peanuts to produce new products that are more efficient and have added value, the community is introduced to the use of social media and the importance of having a product brand so that it's better known to the wider community. So, when living in the age of technology, information on facilities and support possessed by business actors, such as QRIS accounts, is useful when consumers make non-cash transactions. Do not forget too, the importance of business actors in terms of financial management so that they know the development of their business. The result of this community service is that the entrepreneurial competence of the community is growing, such as producing new products, using information technology media as a means of promotion and non-cash transactions as well as financial management insights so that they are able to compete with other businesses.